Murach's ADO.NET 3.5 LINQ and the Entity Framework with C# 2008 - Boehm, Anne (Mike Murach & Associates, 2011)
That's where this book comes in. It shows you how to use Visual Studio 2008 and ADO.NET 3.5 to develop database applications the way the best professionals do.